MANAGEMENT OF ORAL FIBROMA : PENANGANAN FIBROMA PADA RONGGA MULUT - IGN Putra Dermawan; Made Merta Suparka (Interdental Jurnal Kedokteran Gigi (IJKG), 2020)
Introduction: Fibroma is an abnormal tissue growth, formed by hyperplastic reaction of fibrous connective tissue caused of irritation or local trauma to the oral cavity. Clinically this tumor is similar to other connective tissue lesions. Case: A 42-year-old housewife came to RSGM FKG Mahasaraswati Denpasar University with complaints of discomfort of her left cheek and a lump since 4 months ago due to frequent bites. Intra-oral examination revealed a prominent lesion on the left cheek mucosa about 1.2 cm diameters. Case management: After anamnesis, clinical examination and support, the abnormality was diagnosed as Traumatic Fibroma. The patient was referred to Oral Surgery and underwent surgery and suturing. Conclusion: Within 1 week the lesion had healed.